2020
DOI: 10.3390/ani10081367
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oral Supplementation of Different Levels of Tamoxifen on Productive and Reproductive Efficiencies and Carcass Traits of Avian48 and Arbor Acres Broilers

Abstract: This research was aimed at estimating the effect of oral supplementation of Tamoxifen on productive efficiency, carcass characteristics, hormonal profile and gonadal structure of two broiler breeds. One hundred and eighty chicks of each breed of Avian48 and Arbor Acres were divided into three groups: control group; TAM10 group, supplied with 10 mg Tamoxifen/kg of body weight at 3, 5, 7 and 9 days of life; and TAM20 group, supplied at the same intervals with 20 mg Tamoxifen/kg of body weight. Both levels of Tam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 23 publications
(33 reference statements)
4
7
0
1
Order By: Relevance
“…These results indicated that Tam10 might be used to improve griller broiler production Griller‐type chickens are broilers slaughtered between 27 and 29 days old, weighing 1.3 to 1.5 kg and sold as whole carcasses and feed conversion ratio of 1.5 kg of feed per 1 kg of meat (Olivo et al, 2001). Similar results were reported by Younis et al (2020); they investigated the effect of oral supplementation of Tam on productive and reproductive efficiencies and carcass characteristics of two broiler breeds.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…These results indicated that Tam10 might be used to improve griller broiler production Griller‐type chickens are broilers slaughtered between 27 and 29 days old, weighing 1.3 to 1.5 kg and sold as whole carcasses and feed conversion ratio of 1.5 kg of feed per 1 kg of meat (Olivo et al, 2001). Similar results were reported by Younis et al (2020); they investigated the effect of oral supplementation of Tam on productive and reproductive efficiencies and carcass characteristics of two broiler breeds.…”
Section: Discussionsupporting
confidence: 85%
“…These results supported the previous morphological modification in ovarian patterns (Cherici Camargo et al, 2009). Similar results were found in high‐dose TAM treatment in Avian48 (Younis et al, 2020). They found that the number of atretic mature follicles was significantly increased either in the early stage of atresia or the late atretic follicles.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations